Mutual fund flows and government bond returns - Abudy, Menachem Meni; Nathan, Daniel; Wohl, Avi (Journal of Banking & Finance, 2024)
We investigate daily flows to Israeli government bonds mutual funds, which are held primarily by retail investors. We divide the bonds into six categories: nominal/CPI-linked - short-term, intermediate-term, and long-term maturity. We find that unexpected daily net flows are contemporaneously correlated with price changes in all categories, with correlations ranging from 0.094 to 0.221 depending on the bond category. These price changes are significant, and they subsequently reverse fully or mostly within 10 trading days. The price reversal indicates that the initial price changes are due to “price pressure.” We find that these price distortions affect break-even inflation—a measure of inflation expectations. Our findings indicate that even government bonds are affected by retail price pressure.